Obtaining Life-Cycle Cost-Effective Facilities in the Department of Defense - Samaras, Constantine (RAND Corporation, 2013)
The Department of Defense (DoD) constructs, operates, and maintains a large number of facilities. DoD incorporates life-cycle cost-effective practices into many aspects of the military planning and construction processes. This report provides RAND's description and assessment of the process used to obtain life-cycle cost-effective facilities and how that affects DoD construction options and choices.